SIRT1 in the brain—connections with aging-associated disorders and lifespan - Ng, Fanny; Wijaya, Laura; Tang, Bor Luen (Frontiers in Cellular Neuroscience, 2015)
The silent mating type information regulation 2 proteins (sirtuins) 1 of class III histone deacetylases have been associated with health span and longevity. SIRT1, the best studied member of the mammalian sirtuins, has a myriad of roles in multiple tissues and organs. However, a significant part of SIRT1’s role that impinges on aging and lifespan may lie in its activities in the central nervous system (CNS) neurons. Systemically, SIRT1 influences energy metabolism and circadian rhythm through its activity in the hypothalamic nuclei. From a cell biological perspective, SIRT1 is a crucial component of multiple interconnected regulatory networks that modulate dendritic and axonal growth, as well as survival against stress. This neuronal cell autonomous activity of SIRT1 is also important for neuronal plasticity, cognitive functions, as well as protection against aging-associated neuronal degeneration and cognitive decline. We discuss recent findings that have shed light on the various activities of SIRT1 in the brain, which collectively impinge on aging-associated disorders and lifespan.